Comparison of clinical effects of endoscopic powered osteotome and endoscopic powered drill for UBE-TLIF surgery - Wanlong Xu; Haipeng Si; Yulin Zhao (Scientific Reports)
Abstract This study aims to compare the efficacy of two endoscopic instruments powered osteotome and powered drill in treating single-segment degenerative lumbar spinal stenosis via unilateral biportal endoscopic transforaminal lumbar interbody fusion (UBE-TLIF). We retrospectively analyzed clinical data from 127 patients treated at Qilu Hospital of Shandong University between January 2021 and December 2022. Patients were divided into two groups: the bone-drill (BD) group (71 cases) and the bone-osteotome (BO) group (56 cases). Various surgical indicators were assessed, including operation time, intraoperative blood loss, postoperative drainage volume, length of hospital stay, and complication rates. Clinical efficacy was evaluated using the visual analog scale (VAS) for lower back and limb pain, the Oswestry Disability Index (ODI), modified MacNab criteria, and the Brantigan and Steffee method for interbody fusion assessment. Results showed that the BD group had an average operation time of 151.41 ± 19.03 min, whereas the BO group completed the procedure significantly faster, averaging 128.48 ± 16.92 min. Intraoperative blood loss was comparable between groups (BD: 102.11 ± 34.26 ml; BO: 120.70 ± 32.89 ml). The BO group showed higher postoperative drainage volume (85.47 ± 19.01 ml) than the BD group (71.25 ± 14.55 ml). Hospitalization durations were similar (BD: 8.92 ± 1.22 days; BO: 9.16 ± 1.12 days). Both groups showed significant improvement in VAS and ODI scores at 3 and 12 months post-surgery (P < 0.05), with no significant differences between groups (P > 0.05). Notably, the BO group exhibited superior intervertebral fusion quality at 3 months compared to the BD group (P < 0.05), with no differences observed at 12 months. In conclusion, the UBE-TLIF technique employing a powered osteotome significantly reduces operation time and enhances intervertebral fusion compared to the powered drill method.